Augmented Reality in the Science Lab: Enhancing Spatial Understanding of Molecular Structures - Risjunardi Damanik (Journal Emerging Technologies in Education, 2026)
Background. The increasing complexity of scientific concepts, especially in chemistry, poses substantial challenges for students. Understanding molecular structures is particularly difficult due to their abstract and three-dimensional nature. Traditional teaching methods often rely on static visualizations, which can fail to adequately support students' spatial understanding. As a result, learners struggle to visualize molecular components and their relationships in a meaningful way. Purpose. This study aims to explore the effectiveness of Augmented Reality (AR) in improving students’ spatial understanding of molecular structures, particularly in laboratory environments. By leveraging AR’s capacity to enhance visualization and interaction, this research investigates whether it can provide students with a more engaging and effective way to learn complex scientific concepts. Method. A quasi-experimental mixed-methods design was employed, involving 96 undergraduate students. Participants were divided into two groups: an experimental group, which was exposed to AR-based learning, and a control group, which received conventional instruction. The study utilized a combination of quantitative and qualitative data collection methods. Quantitative data were analyzed using t-tests, ANCOVA, and Structural Equation Modeling (SEM), while qualitative data were gathered through interviews and observations. These data points were used to assess the differences in spatial understanding between the two groups. Results. The findings reveal that students exposed to AR-based learning exhibited significantly higher spatial understanding than those who received conventional instruction. Additionally, engagement with AR tools played a mediating role, with students actively interacting with the AR content demonstrating deeper comprehension and improved learning outcomes. This suggests that AR not only aids in visualization but also enhances active learning experiences, which contributes to better educational outcomes. Conclusion. The results indicate that AR is an effective and innovative tool for improving spatial reasoning in science education. By enabling real-time manipulation and visualization of molecular structures, AR supports both the cognitive and experiential aspects of learning. This study concludes that AR has the potential to transform science education by providing a more interactive and engaging way for students to grasp complex scientific concepts.